2016
DOI: 10.1007/s11136-016-1294-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical fitness with health-related quality of life in early postmenopause

Abstract: ObjectiveTo assess the association of different components of physical fitness with HRQoL in early postmenopause and to test which physical fitness components are independently associated with the physical and mental components of HRQoL.MethodsThe final sample comprised 67 early postmenopausal women. Physical fitness was assessed with the Senior Fitness Test battery (additionally including handgrip strength test), and HRQoL was evaluated with the Short-Form Health Survey-36 (SF-36). We also analyzed plasma gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
(36 reference statements)
1
23
0
7
Order By: Relevance
“…Similar associations were also found in the sample of another similar cross-sectional study by Häkkinen et al [9], but without examining muscular and cardiorespiratory fitness separately. Previous studiesmainly with incomparable samples -have particularly highlighted the importance of muscular fitness on HRQoL, for example, among women with autoimmune diseases [4] and in early post-menopause [8] as well as among children [34]. Evidence of cardiorespiratory fitness contributing to the physical well-being dimension of HRQoL has been found in adolescents [35], as well as in young [10] and middle-aged men [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar associations were also found in the sample of another similar cross-sectional study by Häkkinen et al [9], but without examining muscular and cardiorespiratory fitness separately. Previous studiesmainly with incomparable samples -have particularly highlighted the importance of muscular fitness on HRQoL, for example, among women with autoimmune diseases [4] and in early post-menopause [8] as well as among children [34]. Evidence of cardiorespiratory fitness contributing to the physical well-being dimension of HRQoL has been found in adolescents [35], as well as in young [10] and middle-aged men [11].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding the relationship between the level of physical fitness and HRQoL, however, is limited. To date, studies related to this topic have most commonly focused on specific target groups with specific health concerns [3][4][5][6] or conditions [7,8] finding a positive relationship between physical fitness and HRQoL. Only few studies have explored this association in the general adult population [9][10][11], but not separately for muscular and cardiorespiratory fitness.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Lee et al (1999) , although conducted among Korean adolescents, demonstrated the association between mental health and the physical fitness factors of endurance strength and agility. A study conducted in postmenopausal women reported an association between mental health and balance ( Moratalla-Cecilia et al, 2016 ). In a study of depression and physical fitness factors, Ho et al (2008) reported an association between depression and body fat in adult of china.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is synonymous with a study where the researchers noted that natural events in life like menopause can alter the individual's quality of life. Consequently, health-related quality of life (HRQoL), is viewed as a dimension of QoL that deals with the effects of physical, psychological, social and spiritual factors on the overall QoL of individuals [20]. In other words, the QoL identifies four (4) domains (physical well-being such as sleep, social well-being such as family distress, psychological well-being such as depression and spiritual well-being such as hopelessness) that define an individual's QoL.…”
Section: Discussion Of Findingsmentioning
confidence: 99%